Varicella Zoster Meningitis in an Immunized Child - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
A 5-year-old girl with varicella-zoster virus meningitis who had received the VZV vaccine 18 months previously is reported from the University of Chicago.